2013
DOI: 10.3109/14767058.2013.818650
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sildenafil on evolving bronchopulmonary dysplasia in extremely preterm infants: a randomised controlled pilot study

Abstract: In this pilot study, oral sildenafil treatment did not improve any short-term respiratory outcomes in extremely preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In a pilot RCT of 20 infants, four weeks of oral sildenafil solution (3mg/kg/day) was compared to placebo commenced on day seven in mechanically ventilated infants of less than 28 weeks of gestational age. There was no statistically significant difference in BPD at 36 weeks PCA, but a non significant trend for the sildenafil treated group to require more hours of mechanical ventilation and postnatal steroid treatment and they also had a higher respiratory-related mortality [111].…”
Section: Sildenafilmentioning
confidence: 75%
“…In a pilot RCT of 20 infants, four weeks of oral sildenafil solution (3mg/kg/day) was compared to placebo commenced on day seven in mechanically ventilated infants of less than 28 weeks of gestational age. There was no statistically significant difference in BPD at 36 weeks PCA, but a non significant trend for the sildenafil treated group to require more hours of mechanical ventilation and postnatal steroid treatment and they also had a higher respiratory-related mortality [111].…”
Section: Sildenafilmentioning
confidence: 75%
“…However, in 2014, dose-dependent increases in child mortality led to withdrawal of the FDA recommendation for the use of sildenafil in pediatric PH [17]. Furthermore, limited evidence exists for the use of sildenafil as treatment for PH in patients with BPD, and a recent randomized controlled pilot study found that sildenafil treatment did not improve short-term respiratory outcomes [18]. In our retrospective study, the time to normalization of the TR peak velocity and RV morphology increased among patients treated with sildenafil relative to untreated patients, possibly because patients in the former group had more severe PH.…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed by Wardle et al (), sildenafil may possibly both safe and effective in infants with pulmonary hypertension in BPD, and may improve survival if continued until resolution of pulmonary hypertension. However, sildenafil did not improve short‐term respiratory outcomes in a pilot trial of extremely preterm infants as an attempt to prevent BPD (Konig et al, ), suggesting earlier use may not be beneficial. Mourani et al () did a retrospective review of 25 infants with BPD and pulmonary hypertension who received sildenafil, initiated at a median of 171 days (range, 14–673 days) for a median duration of 241 days (range, 28–940 days).…”
Section: Managementmentioning
confidence: 99%